Kemampuan Tepung Talipuk (Nymphaea pubescens Willd) dalam Mensubstitusi Tepung Terigu Pada Kue Cookies - Fatimah Fatimah; Ema Lestari; Dwi Sandri; Melisa Agustina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2019)
Talipuk (Nymphaea pubescens Willd) plant is a local term for lotus plants that are plants that live in areas of swampland in South Kalimantan. This local commodity material may be substituted as an alternative to wheat flour and the potential for flour talipuk to be processed in the manufacture of cookies. The objective of this research is to get the best formulation ratio of flour talipuk in substituting wheat flour in cookies and to analyze the quality of cookies. Cook flour talipuk powder in substituting wheat flour is made with 5 different formulation compositions, 100% wheat flour and 0% flour talipuk, 75% wheat flour and 25% flour talipuk, 50% wheat flour and 50% flour talipuk, 25% wheat flour and 75% flour talipuk, 0% wheat flour and 100% flour talipuk. The results showed that based on organoleptic test, it was found that the best formulation composition was in the treatment of 100% flour talipuk with levels a water 0.88% and ash content of 1.44% has fulfilled SNI 01-2973-1992.